Pengaruh Media Tanam dan PemberianPupuk Pelengkap Cair terhadap Pertumbuhan dan Produksi Tanaman Pakcoy (Brassica rapa L.)dengan Sistem Hidroponik - Miftakhus Surur; Murniati Murniati; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to know the effect of kind of planting media and liquid complementary fertilizer and to know the best treatment on growth and yield of pakcoy plant on hydroponic system. The experiment was conducted in the green house of Faculty of Agriculture Riau University from July to September 2018. This researched experimentally by the form of 3x4 faktorials arranged according to a Complete Randomized Design (CRD)consisting of 2 factors. The first factor was planting media which were charcoal, burnt sawdust and cocopeat. While the second factor was liquid complementary fertilizer of Bayfolan with concentration of 2 and 3 cc.l-1 of waterand Gandasil-D with concentration of 2 and 3 g.l-1 of water. Theparameters observed were the plant height, number of leaves, fresh weight per plant, weight of worth consumption and root volume. The result showed that the giving of various planting media and liquid complementary fertilizerhas a significant effect on plant height, fresh weight and weight of worth consumption, but no significant effect onthe number of leaves and root volume. The aplication of liquid complementary fertilizer of Gandasil-D with a concentration of 3 g.l-1 of water and Bayfolan with a concentration of 3 cc.l-1 of water to the burnt sawdust media produced more leaves, heavier fresh weight and weight of worth consumption than other treatments.Keywords: pakcoy plant, planting media, liquid complementary fertilizer, hydroponic.